Adaptation française du Counselor Rating Form - Bachelor, Alexandra (Canadian Journal of Counselling and Psychotherapy, 2011)
The Counselor Rating Form (Barak & Lacrosse, 1975), assessing three dimensions of helper influence — Expertise, Attractiveness and Trustworthiness — was completed by 230 subjects after viewing films of interviews of three therapists. A factor analysis was performed on the ratings for each therapist and resulted in extraction of three factors. Across the three therapists, the average percentage of total variance accounted for by the three factors was 62%, whereas the average level of internal consistency was. 94. Results strongly replicate those of the original authors and suggest that the French and English questionnaires are highly comparable. The French version of the questionnaire is included.